An enhancement in diesel engine performance, combustion, and emission attributes fueled with Eichhornia crassipes oil and copper oxide nanoparticles at different injection pressures. Issue 3 (14th September 2022) - Khan, Osama; Khan, Mohd Zaheen; Khan, Emran; Bhatt, Bhupendra Kumar; Afzal, Asif; Ağbulut, Ümit; Shaik, Saboor
ABSTRACT: Current scenario of crude oil exhaustion and price rise has motivated researchers to opt and explore other forms of energy which are renewable and sustainable in nature. Waste plant oils have significant potential to become a viable alternative to petro-diesel fuel for transportation and manufacturing purposes. Esterification of unrefined waste oils has significantly addressed the issues mainly occurring due to highly viscous nature of the oil. This analysis aims to conduct a controlled study to examine the impact of injection pressure on the engine parameters amalgamated with copper (III) oxide composites as a nanofuel additive. Biofuel obtained from waste plants (Eichhornia Crassipes) is amalgamated with plain diesel in a 30:70 ratio and copper (III) oxide (Cu2 O3 ) as nano-additive. It is essential to operate the engine over a wide range of injection pressures (180, 200, and 220 bar) for furnishing maximum efficiency when mixed with 90 ppm nano-additive volume fraction. The current analysis shows that the injection of nano-additives raises the injection pressure leads to enhanced engine combustion characteristics, including a maximum peak pressure and a faster heat release rate. At 220 bar, injection pressure with a 90-ppm volumetric fraction of nano-additives yielded superior results in comparison with its counterpart blends. The inclusion of nano-additives for increased injection pressures decreases emissions of hydrocarbon, oxides of nitrogen, and soot particles. Thus, biofuels engines benefit by enhanced injection pressure and decreased emission levels by successfully amalgamating copper (III) oxide as nano-additives. Combined effect of high pressure and nano-additive fuel furnishes a maximal progression of 3.5% in combustion efficacy and a 14% drop in BSEC with reduction of 14% in HC, 15% in NOx, and 15% in smoke.